Gesture Paves the Way for Language Development - Iverson, Jana M.; Goldin-Meadow, Susan (Psychological Science, 2005)
In development, children often use gesture to communicate before they use words. The question is whether these gestures merely precede language development or are fundamentally tied to it. We examined 10 children making the transition from single words to two-word combinations and found that gesture had a tight relation to the children's lexical and syntactic development. First, a great many of the lexical items that each child produced initially in gesture later moved to that child's verbal lexicon. Second, children who were first to produce gesture-plus-word combinations conveying two elements in a proposition (point at bird and say “nap”) were also first to produce two-word combinations (“bird nap”). Changes in gesture thus not only predate but also predict changes in language, suggesting that early gesture may be paving the way for future developments in language.